Nutritional Profile of Medical Students of Tripura and Its Impact on Their Health - Shishir Kumar; Asha Kumari (Medsci Publications, 2013)
Background: Everybody needs a wide range of nutrients to lead a healthy and active life and these are derived through the diet they consume daily. Good nutrition is a basic component of health. The present paper deals with the Nutritional Profile of Medical Students of AGMC, Agartala. Methods: A total of 200 undergraduate medical students (64% males and 36% females) with mean age 20.76(±SD 1.20) years participated in this study. Participants completed a set of questionnaire and pass multiple 24h diet recall. The energy and selected nutrient contents of the food items of medical students constitute sedentary worker group based on the RDA (2010) for Indians by National Institution of Nutrition, Hyderabad. Data were analyzed using SPSS software (version 21). Results: The findings depict that maximum number of 1st year (56.0%) and 2nd year (58.0%) students have energy consumption less than RDA while in 3rd and 4th year students, the percentage having energy consumption greater than RDA was on the high side. In total, the energy consumption of forty five percent of students was found to be less than normal as per RDA. Under-weight males and females consumed only 73.33% and 68.48% vegetables respectively compared to RDA standards. In the present study group in total, the vegetable intake was found to be 68.32% in males and 65.78% in females as compared to RDA standards. Conclusions: The nutritional status of the students of this college was not excellent.